Storm runners - Smith, Roland, 1951- (New York : Scholastic Press, 2011)
Twelve-year-old Chase Masters travels the country with his father, a "storm runner," but he is tested in ways he never could have imagined when he and a new friend are caught in a hurricane near St. Petersburg, Florida.
Reading Counts RC
Accelerated Reader AR
Keywords: Hurricanes -- Juvenile fiction; Storm chasers -- Juvenile fiction; Conduct of life -- Juvenile fiction; Fathers and sons -- Juvenile fiction; Circus animals -- Juvenile fiction; Hurricanes -- Fiction; Conduct of life -- Fiction; Fathers and sons -- Fiction; Circus animals -- Fiction; Saint Petersburg (Fla.) -- Juvenile fiction; Saint Petersburg (Fla.) -- Fiction; Fiction; Juvenile works; Fiction